Motivating Operations and Negative Reinforcement - Edwards, Timothy L. (Perspect Behav Sci, 2020)
The motivating operations concept has improved the precision of our approach to analyzing behavior; it serves as a framework for classifying events that alter the reinforcing and punishing effectiveness of other events. Nevertheless, some aspects of the concept are seriously flawed, thereby limiting its utility. We contend in this article that the emphasis it places on the onset of some stimuli (putative motivating operations) making their offset a reinforcer in the absence of a learning history (i.e., in the case of unconditioned motivating operations), or because of such a history (i.e., in the case of reflexive conditioned motivating operations), is of no value in predicting or controlling behavior. It is unfortunate that this pseudo-analysis has been widely accepted, which has drawn attention away from actual motivating operations that are relevant to negative reinforcement, and led to conceptually flawed explanations of challenging human behaviors that are escape-maintained. When used appropriately, the motivating operations concept can help to clarify the conditions under which a stimulus change (in particular, stimulus termination) will function as a negative reinforcer. From both a theoretical and a practical perspective, rethinking the application of the motivating operations concept to negative reinforcement is advantageous. Herein, we explore the implications of doing so with the aim of encouraging relevant research and improving the practice of applied behavior analysis.